Implantación de la Contabilidad de Costos en la Empresa Industrial Martínez Cueva Marcelo Cristobal del Cantón Gonzanamá, periodo del 01 de abril al 30 de junio del 2023 - Davila Aguilar, Wilma Melania (2024)
The present Curricular Integration Work called Implementation of Cost Accounting in the Industrial Company Martínez Cueva Marcelo Cristobal of Cantón Gonzanamá, period from April 1 to June 30, 2023, was developed with the purpose of informing its owner about the economic and financial situation of the company, so that based on this information he can make the best decisions to allow the proper functioning of the economic entity. In order to fulfill the stated objectives, we began with the visit and analysis of the productive process in the company, which allowed the elaboration of a Plan and Manual of accounts with their respective codification for the easy recognition of the accounts when recording the accounting entries, the through the physical verification and counting of assets, rights and obligations was made the Initial Inventory, which allowed the development of the Initial Situation Statement that on April 1, 2023 had a value of 152.084,53 in Assets, 7.759,99 in Liabilities and 144.324,54 in Patrimony, then the control formats of the cost elements were designed, such as: Cost Sheet, Kárdex Card, Clock Card, Time Cards, Payments and Provisions Role, among others. Then, in a chronological and orderly manner and based on the source documentation, the economic operations were registered on the Daily Journal, next each one of the accounts were transferred to the General Book, and using the balances, the Trial Balance and Worksheet were prepared, and subsequently the Financial Statements were obtained, which reflect the following values: in the Financial Situation Statement on June 30, 2023 was evidenced a value of 159.585,13 in Assets, 8.302,74 in Liabilities and in Patrimony a value of 151.282,39, while in the Statement of Income a net profit for the period of 6.957,86 was obtained. Finally, the conclusions and recommendations are presented based on the results obtained, in order to allow the owner of the company to make appropriate decisions.